PENDAMPINGAN MASYARAKAT MELALUI PENINGKATAN FUNGSI MASJID SEBAGAI PENGUAT UKHUWAH ISLAMIYAH DAN PENDIDIKAN ISLAM BERBASIS NILAI-NILAI RELIGIUS DI DESA AENGDAKE BLUTO SUMENEP - Siti Nurjanah; Iskandar Zulkarnaen (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Mosques at all times must be the construction of the ummah, so that in times of information and reform the mosque must always be able to act as a driver of meeting the spiritual needs of the community. Realizing social services, health and education, fostering children and adolescents, and channeling their talents in the arts and sports, even to the fulfillment of the economic needs of the community. In other words, the mosque must still be able to act as a center for community development and improve Islamic education as the prophet Muhammad (peace be upon him) has exemplified. In other words, the mosque must still be able to act as a center for community development and improve Islamic education as the prophet Muhammad (peace be upon him) has exemplified. Mosque is a place of worship of Muslims, mosque is also very appropriate to be used to increase islamic ukhuwah and as a means to instill islamic education based on religious values. The mosque is also a building that was established as a means to worship Allah Swt. Especially in performing the five times of prayer, other sunnah prayers. But other than that, too. Mosque as a symbol to improve the products of individuals who have good morals and increase knowledge of Islamic treasures. In service to this community. The author uses a community assistance-based approach by using the mosque as a means of increasing religiosity and Islamic ukhuwah. In this study, there are results about the study of Islamic books, the application of prayer together and the procurement of literature books in the mosque area to be read by the surrounding community.